New challenges in the artisanal ice cream market : the marketing strategy to enhance Artisani’s Brand Awareness - Ferreira, Inês de Castro e Brito (2017)
This study aims to find a suitable solution to Artisani’s real-life challenge regarding the lack of brand awareness, theoretically and practically addressing subjects like consumer behavior, brand knowledge, positioning and promotion. Artisani is a Portuguese company, operating in the artisanal ice cream industry for eight years. Recently, Artisani was able to improve its production capacity, so the firm is now focused on increasing brand awareness to raise new customers. Despite having conquered a relevant place in the market, the path to grow and to more closely compete with the market leader must include a strategy that boosts brand knowledge in consumers’ minds. Considering the opportunities brought by the digital environment, Artisani is ready to improve its online presence. Therefore, the problem statement this thesis strives to address is if a digital strategy is the most suitable way to enhance Artisani’s brand awareness. To accomplish this matter, primary and secondary data were collected. It was found that social media is very present in Portuguese consumers’ daily routine and that their purchasing decisions are increasingly influenced by digital factors: consumers are more connected and knowledgeable than ever. While Artisani has strived to be innovative and different, the aimed positioning was not achieved yet. Therefore, a digital strategy proves to be the best way to improve awareness and create unique associations to the brand: not only will it create exposure and engage the target audience, but it will also build trust and loyalty.